CURRENT SITUATION OF NUTRITIONAL CARE IN CHILDREN UNDER 6 MONTHS OF AGE AT VIETNAM NATIONAL CHILDREN’S HOSPITAL IN 2020 (Vietnam Journal of Community Medicine, 2021)
Objectives: To describe epidemiological characteristics, methods of care, the level of physical development of children under 6 months of age to come to the National Children Hospital clinic in 2020. Subject: Mothers and children
Keywords: Nutritional care, children under 6 months.